Increasing product competitiveness of Tempe Chips SMEs through digital marketing - Friztina Anisa; Decka Ari Rahmadhanty; Melati Kusumaning Tyas; Arumsari Okta Irmawati; Narindra Cahya Kusuma Ratri; Leni Islamiati (Universitas Muhammadiyah Magelang, 2022)
This Integrated Community Service Program (PPMT) was implemented for tempe chips SMEs in Manggoran Hamlet, Bondowoso, Mertoyudan. The purpose of this activity is to increase product competitiveness in the form of digital marketing training and labeling, as well as packaging assistance. The methods used in this programs are training and mentoring. From the program, the partner can optimize sales through social media and there is an increase in competitiveness in the form of business branding into Mugi Abadi Tempe Chips, labeling by making business logos and packaging. This service has received a good response from owners with the hope that the business being run can continue to grow.